2022
DOI: 10.1093/ofid/ofac486
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Invasive Fungal Infections in Patients With Previously Untreated Acute Myeloid Leukemia Receiving Venetoclax and Azacitidine

Abstract: Background Acute myeloid leukemia (AML) is associated with a poor prognosis, particularly in elderly patients with comorbidities. Combining azacitidine (AZA) with the BCL-2 inhibitor venetoclax (VEN) demonstrated significant improvement in outcomes for newly diagnosed older AML patients compared to AZA alone. However, this regimen is myelosuppressive, and the incidence of invasive fungal infections (IFI) and impact of antifungal prophylaxis are not well defined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Moving to consolidation chemotherapy, the proportion of our patients experiencing b-IFDs was 1.1% (1/90), lower than in studies conducted before extensive AFP use [ 26 , 60 , 61 , 62 , 63 ] and lower than in the recent study by Del Principe [ 64 ], where AFP was not provided for 44% of patients and the b-IFD incidence among those receiving MAP was 1.5%. Notably, two out of six probable IA in our cohort occurred in patients treated with VEN–HMAs, with 10.5% of patients receiving VEN–HMAs and experiencing b-IFD (2/19), which is similar to the proportion reported in one study [ 57 ] but higher than in other cohorts [ 46 , 75 , 76 , 79 ]. In this setting, some studies [ 46 , 57 ] suggested AFP during initial cycles of induction and in relapsed/refractory AML, while other studies [ 75 , 76 , 79 ] stated there was no need for AFP.…”
Section: Single-center Experience With Posaconazole Prophylaxis In Pa...supporting
confidence: 85%
See 1 more Smart Citation
“…Moving to consolidation chemotherapy, the proportion of our patients experiencing b-IFDs was 1.1% (1/90), lower than in studies conducted before extensive AFP use [ 26 , 60 , 61 , 62 , 63 ] and lower than in the recent study by Del Principe [ 64 ], where AFP was not provided for 44% of patients and the b-IFD incidence among those receiving MAP was 1.5%. Notably, two out of six probable IA in our cohort occurred in patients treated with VEN–HMAs, with 10.5% of patients receiving VEN–HMAs and experiencing b-IFD (2/19), which is similar to the proportion reported in one study [ 57 ] but higher than in other cohorts [ 46 , 75 , 76 , 79 ]. In this setting, some studies [ 46 , 57 ] suggested AFP during initial cycles of induction and in relapsed/refractory AML, while other studies [ 75 , 76 , 79 ] stated there was no need for AFP.…”
Section: Single-center Experience With Posaconazole Prophylaxis In Pa...supporting
confidence: 85%
“…These targeted therapies led to an improvement in OS, with a higher achievement of CR in subgroups of patients with historically poor outcomes [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. The incidence of IFDs with these new therapies is largely variable [ 55 , 75 , 76 ], and few data are available on the need for and efficacy of AFP. In addition, DDIs between azoles and these new molecules, mainly driven by the strong inhibition of cytochrome P450 3A4 [ 77 ], make the choice of AFP even more difficult and heterogeneous between centers.…”
Section: Invasive Fungal Diseases In Patients Undergoing Remission In...mentioning
confidence: 99%
“…Findings from single institution studies can be difficult to extrapolate. Our newlydiagnosed AML patients receiving venetoclax + azacitidine do not routinely receive antifungal prophylaxis due to our reported low rates of proven or probable invasive fungal infections in this population (29). We are also likely outliers with respect to our aggressive approach to ASCT in venetoclax+azacitidine patients (30).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of pharmacokinetic evidence and recommendations [46][47][48] for VEN dose reduction with concomitant azole administration, clinical conduits regarding antifungal prophylaxis vary greatly among different institutions. Although mainly derived from experiences with VEN + HMA as first-line treatment for AML, currently available data suggest that the rate of IFIs in patients receiving VEN + HMA is generally low (5%) [49]. However, in a report by Aldoss et al [50], a 19% incidence of IFIs was reported among patients receiving VEN + HMA for R/R AML, with both R/R status and refractoriness to VEN + HMA independently associated with an increased risk of IFI.…”
Section: Venetoclax + Hmas or Ldac For R/r Amlmentioning
confidence: 99%